Uterus human leucocyte antigen expression in the perspective of transplantation. Issue 12 (19th September 2016) - Gauthier, Tristan; Filloux, Matthieu; Guillaudeau, Angelique; Essig, Marie; Bibes, Romain; Pacha, Adam Fodil; Piver, Pascal; Aubard, Yves; Marquet, Pierre; Drouet, Mireille
Abstract: Aim: To describe class I and II human leucocyte antigen (HLA) expression using different uterine tissues in the perspective of uterus transplantation. Methods: Human uterine tissues were obtained from 12 women who had undergone hysterectomy for the treatment of benign disease. HLA class I and HLA‐antigen D related (DR) expression were assessed via immunochemistry. HLA class I expression in the uterus was compared with expression in other organs and tissues, including kidney and myocardium samples. Results: HLA class I expression was strong in the endometrial glands and mild in the myometrium. Staining of endometrial glands was similar to glomerular staining in the kidney. The myometrium seems to express HLA class I similarly to hepatocytes and myocardial cells. HLA class I expression in the uterus did not differ in younger or post‐menopausal women. HLA‐DR was expressed in the endometrial glands, but not in the myometrium. A lack of HLA‐DR expression seemed to be correlated with cell proliferation. Conclusion: HLA expression in the endometrium and myometrium is different. The endometrium should be the major target of alloreactive response. As for other transplanted organs, assessment of HLA unacceptable antigens and multiple immunosuppressive treatments is necessary in uterus transplantation.